Blue magic : the people, power, and politics behind the IBM personal computer - Chposky, James; Leonsis, Lynn M. (New York : Facts On File Publications, 1998)
The text is based on interviews with senior members of the original team commissioned to do something that had never been done before at IBM: within one year, to design, develop and bring tp market a singualr-ly outstanding machine that would anchor IBM in what was for for the company a new niche in its industry.
1. The vixen and the rocket -- 2. Putting a toe in the water -- 3. Assaying the golden apple -- 4. Riding the fast track -- 5. The finest task force assembled -- 6. Essential approvals -- 7. Just call me "Don" -- 8. Tasks at hand -- 9. Microsoft meets IBM -- 10. Choosing the operating system -- 11. Tying loose ends -- 12. A "true blue" family -- 13. The pace quickens -- 14. The peddler is a tramp -- 15. Choosing the mail carrier -- 16. Bidding for bucks -- 17. The inner circle -- 18. The emergency brigade -- 19. The shroud of secrecy -- 20. Riding the crest -- 21. Surviving with success -- 22. An interlude for intrigue -- 23. Validating the acclaim -- 24. Discontent and defection -- 25. Into bureaucracy -- 26. Hubris and humility -- 27. Where all roads lead -- 28. Dealing with disaster -- 29. IBM moves in -- 30. An erosion of autonomy -- 31. Estridge moves on -- 32. The dark day at dallas -- 33. The last man out.
Includes index.
Keywords: INTERNATIONAL BUSINESS MACHINES CORPORATION -- HISTORY